Malfunctioning Plastic Biliary Endoprosthesis: Percutaneous Transhepatic Balloon Pulling Technique - Umberto G. Rossi; Paolo Rigamonti; Maurizio Cariati (Case Reports in Radiology)
Percutaneous transhepatic removal techniques for malfunctioning plastic biliary endoprosthesis are considered safe and efficient second-line strategies, when endoscopic procedures are not feasible. We describe the percutaneous transhepatic balloon pulling technique in a patient with an unresectable malignant hilar cholangiocarcinoma.